2017
DOI: 10.1089/ham.2016.0119
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Acute Hypobaric Hypoxia

Abstract: Irarrázaval, Sebastián, Claudio Allard, Juan Campodónico, Druso Pérez, Pablo Strobel, Luis Vásquez, Inés Urquiaga, Guadalupe Echeverría, and Federico Leighton. Oxidative stress in acute hypobaric hypoxia. High Alt Med Biol. 18:128-134, 2017.-The effects of acute hypobaric hypoxia endured by mountaineers were studied, specifically as evidenced by acute mountain sickness (AMS) and oxidative stress damage. Ten male volunteers were exposed to acute hypobaric hypoxia, and AMS was evaluated through arterial oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 26 publications
0
30
0
2
Order By: Relevance
“…Our study found that exposure to high altitude resulted in upregulation in the expression of in ammatory cytokines and downregulation anti-in ammatory cytokines expression [7]. Moreover, hypobaric hypoxia induces oxidative damage and decreases antioxidative functions [20]. Considering metabolic modulation, glycolytic capacity is promoted and oxidative metabolism is suppressed in response to hypoxia [21,22].…”
Section: Discussionmentioning
confidence: 88%
“…Our study found that exposure to high altitude resulted in upregulation in the expression of in ammatory cytokines and downregulation anti-in ammatory cytokines expression [7]. Moreover, hypobaric hypoxia induces oxidative damage and decreases antioxidative functions [20]. Considering metabolic modulation, glycolytic capacity is promoted and oxidative metabolism is suppressed in response to hypoxia [21,22].…”
Section: Discussionmentioning
confidence: 88%
“…The present study is the first to assess gCBF after acclimatization to altitude with and without the use of antioxidants. There are well‐reported elevations in oxidative stress with normobaric (Irarrázaval et al., ) and hypobaric hypoxia (Bailey et al., ; Lewis et al., ). Therefore, it is reasonable to hypothesize that this increase in oxidative stress might, in part, be responsible for the alternations in cerebral vascular function at high altitude (Jensen, Sperling, Severinghaus, & Lassen, ).…”
Section: Discussionmentioning
confidence: 97%
“…Elevated markers of oxidative stress are evident in both acute (Irarrázaval et al., ) and chronic hypoxia (Lewis et al., ), which may lead to a reduction in nitric oxide (NO) bioavailability through the interaction of NO and superoxide (i.e. free radical [O 2 − ]) to form peryoxynitrite (O 2 − + NO = ONOO − ; Meli, Nauser, Latal, & Koppenol, ; Thomas, Witting, & Drummond, ).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between oxidative stress and AMS severity has also been suggested. [15][16][17] Releases of both inflammatory mediators and ROS would lead to the disruption of blood brain barrier (BBB), inducing the capillary leakage and finally causing the cerebral edema (BBB theory). 3 As the leading cells in host response, neutrophils undoubtedly play an important role in the complex networks.…”
Section: Discussionmentioning
confidence: 99%